2022
DOI: 10.3390/biology11010061
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Symptoms in COVID-19 Patients: Insights into Pathophysiology and Risk Factors of Long COVID-19

Abstract: There is growing evidence of studies associating COVID-19 survivors with increased mental health consequences. Mental health implications related to a COVID-19 infection include both acute and long-term consequences. Here we discuss COVID-19-associated psychiatric sequelae, particularly anxiety, depression, and post-traumatic stress disorder (PTSD), drawing parallels to past coronavirus outbreaks. A literature search was completed across three databases, using keywords to search for relevant articles. The caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
109
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 187 publications
(291 reference statements)
8
109
0
1
Order By: Relevance
“…It is unclear what the precise causes of long COVID or neuropsychiatric symptoms could be the result of neuroinvasion by coronavirus in the brain and CNS or could result from systemic inflammation or a combination of both. There are conflicting studies regarding the specific ability of coronaviruses to cross the blood-brain barrier and infect the CNS or to be transmitted from neuron to neuron via the olfactory bulb ( Thye et al, 2022 ). However, clinical observations of anosmia and encephalitis would suggest that SARS-CoV-2 and other coronaviruses are capable of both ( Mondelli and Pariante, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear what the precise causes of long COVID or neuropsychiatric symptoms could be the result of neuroinvasion by coronavirus in the brain and CNS or could result from systemic inflammation or a combination of both. There are conflicting studies regarding the specific ability of coronaviruses to cross the blood-brain barrier and infect the CNS or to be transmitted from neuron to neuron via the olfactory bulb ( Thye et al, 2022 ). However, clinical observations of anosmia and encephalitis would suggest that SARS-CoV-2 and other coronaviruses are capable of both ( Mondelli and Pariante, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with other research on pre-infection health behaviours is difficult due to their being a lack of research in this area. Research on pre-infection factors influencing long COVID has focused on health conditions such as obesity, asthma, and higher pre-pandemic levels of psychological distress, 4,710 but research on health behaviours, which may be more amenable to intervention, is largely absent. Several of the health behaviours we examined, such as not smoking, a healthy diet, regular physical activity, and consuming fewer than 14 alcoholic drinks per week are all inversely associated with all-cause mortality and longer lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of smokers in England decreased over the period 2011 to 2019 from 19.8% to 13.9%, certain groups continue to be more likely to smoke: people with a mental health condition and those working in lower skilled occupations. 16 Lower socio-economic status and pre-existing mental health conditions have both been found to be risk factors for developing long COVID, 4,10,33 underscoring the importance of smoking cessation particularly for vulnerable groups. Some long COVID management guidelines recommend not smoking to manage symptoms such as breathlessness, 41 but this advice is currently only within a subsection of the National Health Service's COVID recovery guidance for patients which advises people to avoid smoking or vaping near their oxygen tank at home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection with SARS-CoV-2 is, in itself, associated with psychological consequences, including depression, anxiety, stress and adjustment disorders, poorer sleep, increased substance use, and increased use of antidepressants and opioids. [7][8][9][10] Whilst psychological symptoms generally improve over time, some can linger for substantial periods of time (such as 1 year) without much improvement, or can even worsen over time. 12,13 When focusing specifically on long Covid, a meta-analysis of 39 studies including over 10,000 people found that 19% of people with long Covid reported anxiety and 8% depression as one of their symptoms.…”
Section: Introductionmentioning
confidence: 99%